AKULTURASI SENI PERANAKAN TIONGHOA-MAKASSAR - Sari, Helvi Mei; Sudirman, Feby Dehmi; Sofyan, Sofyan (Nuansa Journal of Arts and Design, 2020)
This study is a qualitative study using objective approach. Research objectives of this study are describing the historical background of Chinese in Makassar and acculturation of Makassarese Chinese in the field of art. The data is collected through interview, observations, and review of literature. In processing the data, there are three techniques used: (1) Data Reduction; (2) Display Data; and (3) Conclusion Drawing and Verification. The results of the study reveal that Chinese came to Indonesia since centuries ago during dynastic war in Cina. They came in Makssar during Dinasti Tang on 15th. They came gradually and began to settle in Makassar during the reign of Kerajaan Gowa. This was the beginning of acculturation. At the time, they mingle with indigenous people and began to pursue various fields, including in art and culture. In music, one of Chinese named Ho Eng Djie was famous for his songs such as Amma Ciang or Atti Raja. In addition, a Chinese writer was famous with his work, Pantoen Melajoe Makassar.